2022
DOI: 10.1186/s12864-021-08229-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of histone deacetylases and their roles in response to abiotic and PAMPs stresses in Sorghum bicolor

Abstract: Background Histone deacetylases (HDACs) play an important role in the regulation of gene expression, which is indispensable in plant growth, development, and responses to environmental stresses. In Arabidopsis and rice, the molecular functions of HDACs have been well-described. However, systematic analysis of the HDAC gene family and gene expression in response to biotic and abiotic stresses has not been reported for sorghum. Results We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Overall, the average intron number is 0.688 per gene, comparable to the value in genome-wide (0.60) ( Wang et al., 2020 ), but much less than the value of their plant counterparts [ranging from 0 to 78 in Arabidopis ( Wang et al., 2020 )]. Besides, a similar gene structure was observed in gene members from the same subgroup in plant HAT s and HDAC s ( Pandey et al, 2002 , Liu et al., 2012 ; Du et al., 2022 ). Accordingly, Py10301 and Py03239 , being the closet members from the Class I- HDA subfamily, both had two introns, despite of a longer 3 rd exon in Py03239 .…”
Section: Resultssupporting
confidence: 67%
“…Overall, the average intron number is 0.688 per gene, comparable to the value in genome-wide (0.60) ( Wang et al., 2020 ), but much less than the value of their plant counterparts [ranging from 0 to 78 in Arabidopis ( Wang et al., 2020 )]. Besides, a similar gene structure was observed in gene members from the same subgroup in plant HAT s and HDAC s ( Pandey et al, 2002 , Liu et al., 2012 ; Du et al., 2022 ). Accordingly, Py10301 and Py03239 , being the closet members from the Class I- HDA subfamily, both had two introns, despite of a longer 3 rd exon in Py03239 .…”
Section: Resultssupporting
confidence: 67%
“…Sequence alignments indicated that ZmHDT103 exhibited high identities with the homologous sequences of SbHDT2, ObHDT2, AtHD2C, GhHDT4D, AtHD2A, and AtHD2B (Figure S1). Moreover, SbHDT2 controlled cell growth under abiotic stress and showed increased acetylation levels when exposed to abiotic stresses [32]. These results indicated that ZmHDT103 may be involved in the response of maize to abiotic stresses.…”
Section: Phylogenetic Analysis and Drought Stress Responsiveness Of Z...mentioning
confidence: 75%
“…Similarly, Arabidopsis AtSRT2‐CDS3 negatively regulates the resistance against Pseudomonas DC3000 . In addition, the expression levels of sorghum SbSRT1 and SbSRT2 were significantly increased after induction with exogenous chitin (Du et al, 2022). In this study, knockout of FvSRT1 resulted in enhanced defence response against B. cinerea in strawberry plants accompanied by significant upregulation of numerous biotic stress genes ( MBL1 , PAL1 , PGIP , TLP1b ) and antioxidant enzyme genes ( SOD , CAT ).…”
Section: Discussionmentioning
confidence: 99%
“…Transient OE of FaSRT1-2 in strawberry fruitReferring to the method proposed ofChen et al (2022), a pair of specific primers were designed for amplifying the full-length CDS of FaSRT1-2. Subsequently, the amplified sequence was efficiently ligated into an OE vector pCAMBIA1301 by double digestion with XbaI and BamH I enzymes.…”
mentioning
confidence: 99%